Efficacy of carbonyl cyanide-3-chlorophenylhydrazone in combination with antibiotics against Mycobacterium abscessus - Jifang Zheng; Qiang Liu; Haoran Wang; Fengmin Huo; Junnan Jia; Hairong Huang; Suting Chen (Microbiology Spectrum)
ABSTRACT Given the intrinsic resistance of Mycobacterium abscessus to a wide range of conventional antibiotics, it is urgent to explore new therapeutic approaches to manage this infection effectively. Carbonyl cyanide 3-chlorophenylhydrazone (CCCP), a proton pump inhibitor, has shown good bacteriostatic activity against M. abscessus. This study aimed to determine its synergistic antimicrobial effects when combined with commonly used antibiotics. The M. abscessus reference strain and 39 clinical isolates were collected. The minimum inhibitory concentration and fractional inhibitory concentration index were determined for the combined treatment using CCCP with various antibiotics including clarithromycin, amikacin, linezolid, bedaquiline, and clofazimine. A time-killing assay was used to measure the effect of the combined drug regimens quantitatively. The simultaneous use of CCCP with traditional antibiotics shows a synergistic effect across a wide range, significantly boosting the ability to inhibit the growth of M. abscessus throughout its growth phases. When CCCP is used in combination with clarithromycin, amikacin, and linezolid, it produces a synergistic effect on both the standard strain and most clinical isolates. When CCCP is paired with bedaquiline and clofazimine, it exhibits additive effects. Moreover, high levels of CCCP in combination with other antibiotics were found to rapidly eradicate the bacteria. The use of CCCP as a potential treatment for M. abscessus infections shows promising results, especially when combined with other antibiotics to achieve a potent bactericidal effect.IMPORTANCEMycobacterium abscessus poses a significant public health threat due to its intrinsic resistance to a broad spectrum of conventional antibiotics. This resistance necessitates urgently exploring novel therapeutic strategies to effectively combat infections caused by this pathogen. Our previous research has identified carbonyl cyanide-3-chlorophenylhydrazone (CCCP) as a potent direct antimicrobial agent against M. abscessus and as an enhancer of clarithromycin activity. Our results demonstrate that the concurrent administration of CCCP with traditional antibiotics exhibits a synergistic effect across a wide range, which could be crucial for overcoming the challenges posed by M. abscessus infections. Furthermore, the use of high concentrations of CCCP in combination with other antibiotics was found to rapidly eliminate M. abscessus, suggesting a potential therapeutic advantage. These insights not only advance our understanding of antimicrobial synergy but also hold promise for the development of more effective treatment regimens against drug-resistant M. abscessus infections.